Accelerating The Adoption of Technological Innovations through of Hybrid Paddy Varieties in Bone District, South Sulawesi - Mikhael; Aziz, Muhammad Abdul; Nursyamsi, Dedi (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2025)
Demonstration Farming is one method of delivering research results and studies to farmer and other users through technology demonstrations to accelerate technology adoption. The purpose of disseminating technological innovation of new superior varieties of hybrid paddy through demonstration farming is to accelerate technology adoption. The activity was carried out in Mandiri Farmer Group, Mallinrung Village, Libureng District, Bone Regency, South Sulawesi. The implementation time started from May to September 2022. The hybrid paddy cultivation technology package was carried out using the Integrated Crop Management (ICM) approach. Variables observed included: 1). Implementation of hybrid paddy demfarm technology innovation, 2). Rice productivity, and 3). Technology dissemination and adoption opportunities. The results of the activity showed that the paddy Demfarm implemented by Mandiri farmer group through the introduction of hybrid varieties combined with ICM approach was able to increase the average productivity of rice by 11.23 tons.ha-1 or 106.73% of the average initial productivity of 5.43 tons.ha-1. Technology dissemination through paddy demfarm and farmer field meetings gave a good response to farmers participating in demfarm and other farmers both in implementation location area and farmers outside the area. Farmers and extension workers can witness firsthand and feel confident in the superiority of technology being demonstrated. Demfarm paddy technology innovations that are likely to be adopted based on the result of interviews include: the use of hybrid varieties (92%), integrated pest control according to target pest organism (90%), the use of quality/ certified seeds and seed treatment (88%), Balanced fertilization (84%), and complete tillage system (80%).